Strongyloidiasis: the most neglected tropical disease in Ethiopia - Abebaw Tiruneh; Endalew Zemene; Zeleke Mekonnen (BMC, 2021)
Abstract Background Strongyloidiasis is the most neglected of the neglected tropical diseases (NTDs). The aim of this commentary is to describe the possible reasons why strongyloidiasis is so overlooked in Ethiopia, and shed light on better ways of control and elimination of the disease. Main body This commentary highlights three points why strongyloidiasis is the most neglected of the NTDs in Ethiopia. Firstly, lack of clear category within the NTDs resulted in omission of the disease from reports, intervention programs, and preventive chemotherapy guidelines. Secondly, magnitude of the disease is underestimated due to paucity of studies and low sensitivity of diagnostic methods coupled with asymptomatic nature of most of the infections. Finally, ivermectin (the drug of choice for treatment of strongyloidiasis) is not in use for control of the other soil-transmitted helminthiasis, nor is there ivermectin mass drug administration for control of strongyloidiasis. This might have created gap in control and elimination of the disease in Ethiopia and possibly elsewhere. Conclusion Strongyloidiasis appears to be the most neglected of the NTDs mainly due to nature of the infection, low sensitivity of the routine diagnostic tools and it's exclusion from strategic plans and intervention programs. Moreover, studies on strongyloidiasis should use sensitive diagnostic tools. Strongyloidiasis control and elimination programs should be based on reliable evidence of epidemiology of the disease in Ethiopia. Graphic Abstract